1994
DOI: 10.1111/j.1432-1033.1994.tb18722.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of rat acid phosphatase complexed with the transition‐state analogs vanadate and molybdate

Abstract: The three-dimensional structures of complexes of recombinant rat prostatic acid phosphatase with the transition-state analogs vanadate and molybdate were determined to 0.3-nm resolution using protein crystallographic methods. The overall structure of the enzyme remains unchanged upon binding of the metal oxyanions; only local conformational differences in the positions of some side chains at the active site were found. The metal oxyanions bind in an identical fashion at the active site with trigonal bipyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 20 publications
(20 reference statements)
7
125
0
4
Order By: Relevance
“…2B). The phosphorus atom is at a favorable distance for nucleophile attack by His 12 , leading to the dephosphorylation of IQ 2-P to IQ 2-OH , in agreement with the theoretical axial attack of P by this nucleophile (24,25). The iodine atom of the quinazolinone points outward from the active site and does not hinder the binding to PAP.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…2B). The phosphorus atom is at a favorable distance for nucleophile attack by His 12 , leading to the dephosphorylation of IQ 2-P to IQ 2-OH , in agreement with the theoretical axial attack of P by this nucleophile (24,25). The iodine atom of the quinazolinone points outward from the active site and does not hinder the binding to PAP.…”
Section: Resultssupporting
confidence: 65%
“…2A) 18 and Trp 174 as in the case of the crystallized complex. Furthermore, the docking position of the phosphorus atom of the phosphonic group of BABPA is close to the crucial His 12 as seen in the crystal structure complex or in other phosphate-based inhibitors (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, none of the receptor or nonreceptor PTPs reported to date possess a phosphate at the catalytic site. Several PTPs have been crystallized with the phosphate mimetics vanadate and sulfate that are localized at a similar position to the phosphate group on PTPL1 (27)(28)(29)(30). It is believed that the WPD loop in PTPs moves into a "closed" conformation when substrates bind (31).…”
Section: Resultsmentioning
confidence: 99%
“…Most plant and fungal phytases belong to the histidine acid phosphatases, which share the same amino acid sequence motif (RHGXRXP) at their active sites as acid phosphatases and nucleotidases (van Etten et al, 1991;Oh et al 2004;Kostrewa et al, 1997Kostrewa et al, , 1999Lim et al, 2000). The amino acid sequence motif at the active site of phosphatases drives the reaction mechanisms, which can lead to either the incorporation of an oxygen atom derived from a water molecule into the newly formed phosphate (Lindqvist et al, 1994;Knöfel and Sträter, 2001;Ortlund et al, 2004), e.g., acid phosphatases or nucleotidases, or to the incorporation of an oxygen atom derived from a hydroxide ion, e.g., alkaline phosphatases (Kim and Wickoff, 1991;Stec et al, 2000). It has been suggested that these two types of reaction mechanisms are the reason why different phosphomonoesterases cause different isotopic fractionations (von Sperber et al, 2014).…”
Section: Comparison Of Phytase To Acid Phosphatase Oxygen Isotope Framentioning
confidence: 99%